CTNI-60. PRELIMINARY RESULTS OF BINIMETINIB AND ENCORAFENIB IN ADULTS WITH RECURRENT BRAF V600E-MUTATED HIGH-GRADE GLIOMA. (14th November 2022) - Schreck, Karisa; Strowd, Roy; Nabors, L Burt; Ellingson, Ben; Fisher, Joy; Desideri, Serena; Danda, Neeraja; Rudek, Michelle; Grossman, Stuart; Ye, Xiaobu
Abstract: BACKGROUND: Although < 5% of high-grade gliomas (HGG) are BRAF-V600E mutated, these tumors are being identified more frequently as genetic testing increases in gliomas. Given the treatment-refractory nature HGG, RAF-targeted therapy is of special interest. The combination of encorafenib (BRAF inhibitor) with binimetinib (MEK inhibitor) was evaluated in adults with recurrent BRAFV600-mutated HGG. METHODS: In this phase 2, open-label, Adult Brain Tumor Consortium trial(NCT03973918) encorafenib (450mg daily) and binimetinib (45mg twice daily) were administered continuously until disease progression, unacceptable toxicity, or death. Eligible patients had a histologically-confirmed HGG with BRAF-V600E mutation identified by PCR or next generation sequencing, and had progressed after radiation and any number of prior medical therapies. The primary endpoint was radiographic response rate by RANO criteria. Plasma was collected at baseline, on-study, and at progression for correlatives. RESULTS: Five patients enrolled between January 2020 and November 2021. All patients had at least one prior recurrence (range 1-4) and received radiation one or more times. Median age was 27 years(range 22-77). Histopathologic diagnosis was glioblastoma(n = 2), anaplastic PXA(aPXA; n = 2), and anaplastic ganglioglioma(aGG; n = 1). Patients received treatment for 2-28months; currently 2/5 patients remain on treatment (8 and 30 months). Radiographic response rate was 60%(3/5): CR in two (glioblastoma, treated 10months; glioblastoma, 8months treatment ongoing), PR in one (aPXA, 28months treatment ongoing), SD in one (aGG, treated 3months), and PD in one (aPXA, treated 2months). Likely attributable adverse events (CTCAE grade ≥ 3) included cilioretinal artery occlusion (came off study) and asymptomatic elevated CPK. Analysis of paired plasma samples and correlation with response is ongoing. CONCLUSIONS: Encorafenib and binimetinib demonstrate promising tumor responses in patients with recurrent BRAFV600E-mutated HGG with sustained responses in all GBM and 50% of aPXA in this small series, warranting careful consideration in this rare tumor subgroup. This Phase 2 study has closed due to enrollment issues